The Economics of Money, Banking, and Financial Markets - Frederic Mishkin (Pearson Education Limited, 2024)
The Economics of Money, Banking, and Financial Markets, Business School Edition, presents a more finance-oriented approach—an approach more commonly taught in business schools, but also one that some professors in eco-nomics departments prefer when teaching their money and banking courses. The Business School Edition includes chapters on nonbank finance, financial deriva- tives, and conflicts of interest in the financial industry. The Business School Edition omits the chapters on the IS curve and the monetary policy and aggregate demand curves, as well as the chapter on the role of expectations in monetary policy. The Economics of Money, Banking, and Financial Markets, Business School Edition, will more closely fit the needs of those professors whose courses put less emphasis on monetary theory.